INTERDEPENDENT ANALYSIS OF LEVERAGE, DIVIDEND, AND MANAGERIAL OWNERSHIP POLICIES: Agencies Perspectives - Wibisono Hardjopranoto (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2006)
This paper attempts to investigate interdependent mechanism among leverage, dividend, and managerial ownership policies. This paper considers firm size and economic conditions to control their effect on the relationship among the three policies. The interrelationship between leverage, dividend, and managerial ownership policies will be tested using two-stage least squares. Five exogenous variables are employed in simultaneous equation: current assets and structure of assets as leverage determinants, book to market and return on investment as dividend determinants, and relative return to risk as managerial ownership determinant. The research employs year 1994-2004 data, with 1717 firm years. The research findings can be summarised as follows. First, there is a negative relationship between managerial ownership and leverage policies as suggested by agency theory. Second, there is a relationship between managerial ownership and dividend policies, but the relationship between leverage and dividend is insignificant. Third, the relationship between leverage and dividend is insensitive to economic condition and firm size. Fourth, all exogenous variables have significant effect on endogenous variables, except relative return. Fifth, the effects of exogenous variables are not sensitive to control variables. Sixth, we find that managers show self-interest behaviours by reducing managerial ownership when the economic condition worsens.